Interrogating the Intersections Between General and Special Education in the History of Teacher Education Reform. (September 2018) - Blanton, Linda P.; Pugach, Marleen C.; Boveda, Mildred
This article provides an historical analysis of major reforms in teacher education, beginning in the 1970s, specifically focusing on the opportunities each reform presented to build a shared agenda across pre-service general and special education, and the constraints that operated on them. The analysis revealed the existence of several such intersections, each of which created substantive occasions for joint action across general and special education at every stage of teacher education reform. However, four factors— policy, funding, timing, and norms of separation —appear to have operated as constraints upon mining the capacity of these potential intersections. If the promise of a cohesive system of education capable of and committed to supporting struggling students across multiple and intersecting diversities is to be realized, it will be critical to coalesce around a comprehensive equity agenda that builds on the intersections that continue to exist between general and special education.